Práticas da leitura e usos do livro didático de História na cultura da EMEF Jardim Guarani - Garcia, Liz Araujo Martins [UNIFESP] (2019)
This Master´s thesis researched the reading practices of History didactic books in Jardim Guarani – Professor José Alfredo Apolinário School. The main objective of this research was observe types of the treatment and reading comprehension of the didactic books. For this purpose, this research was based on some assumptions: 1.The concept of School shape, which presume principles of writing culture, that is to say, reading and writing skills. 2. The School Culture that consolidated the didactic book as the main educational material of School. 3. The History as a subjective whose peculiarity is to denaturalize structures. 4. The book production and its text editing move some reading devices. The relation between students and this didactic book’s reading device is autonomous, more than that is assumed. The source analyzed were constructed as of scouting report about the reading of didactic book at the classroom, questionnaires and interviews with teachers and students. Even though this Master’s thesis is not about oral History since that was not the methodology used. The questionnaires and the interviews were used as opposed to the questions and issues that emerged during the observation.